Comparison of proteinuria determination by urine dipstick, spot urine protein creatinine index, and urine protein 24 hours in lupus patients - Thanyaluk Chotayaporn (2018)
Background: A simple, convenient, and accurate method for detecting urine protein excretion in lupus nephritis is crucial. Objectives: The objectives of the study were to determine the sensitivity and the specificity of the qualitative urine dipstick test value to detect 0.50 g or greater of the quantitative 24-hour urine protein (24-hUP) in lupus patients, to evaluate an overall agreement of the dipstick test results and the magnitude of 24-hUP, and to examine the correlation between the spot urine protein creatinine index (S-UPCI) and the 24-hour UPCI with that of the 24-hUp. Methods: A prospective study was conducted in 92 patients with lupus. All dipstick test values from 5 dipstick assays (Bayer, Roche, Meditest USA, Standard Diagnostics, and Arkray) and the S-UPCI were obtained within 6 hours of the 24-hUP collection. Of 149 urine samples, only 39% were collected properly and were used for analysis. Results: The sensitivity and specificity of a ≥2+ dipstick test result to detect 0.50 g or greater 24-hUP were 56-% to 80% and 67% to 92%, respectively. The agreement of the urine dipstick test values and the magnitude of 24-hUP was fair (κ = 0.23-0.32). The correlation between the S-UPCI and the 24-hUP was 0.83 (P < 0.0001), and that of the 24-hour UPCI and the 24-hUP was 1 (P < 0.0001). Using 24-hUP 2 g/d or less, the bias ±1.96 SD of the difference of S-UPCI and 24-hUP was 0.23 (SD, 0.96) g. Conclusions: A ≥2+ dipstick test is relatively sensitive to detect significant proteinuria, but it is poorly correlated with quantitative 24-hUP. The S-UPCI and the 24-hUP can be used interchangeably for follow-up in lupus nephritis patients with proteinuria of less than 2 g/d. Copyright © 2011 Lippincott Williams & Wilkins.